Endangered mothers or 'anchor babies'? Migration motivators for pregnant unaccompanied Central American teens. Issue 4 (2nd October 2018) - Schmidt, Susan
ABSTRACT: As politicians grapple with global migration policies, traditionally sympathetic populations such as pregnant migrant women now evoke suspicion and fear, evident in US usage of the disparaging term 'anchor babies.' Using secondary interview data, this article compares the migration motivations of 11 pregnant unaccompanied teens from Honduras, El Salvador, and Guatemala with the 'anchor baby' assumptions. Results reveal migration motivation themes of safety concerns, desire for US opportunities, and assistance of a US-based relative. Nine of the 11 teens revealed safety concerns for themselves or their child, largely as a consequence of sexual and gender-based violence. A beginning model of migration for pregnant Central American teens is proposed. Practice implications include sensitivity to the possibility of sexual and gender based violence prior to migration, use of varied questioning to reveal such experiences, the connection between safety concerns and US legal protections, and the need to debunk erroneous political rhetoric.